Arusha & Lake Manyara national parks [videorecording (DVD)] - Watt, Kelly, 1962-; Watt, Jim, 1943-; Brown, Mason B. E. (Discoveries-- Africa. Tanzania., 2009)
Features national parks, Arusha, Mto Wa Mbu School, colobus monkey, tree climbing lions and other wild game animals.